THE EFFECTIVENESS OF NURSE-LED DEMENTIA CARE INTERVENTIONS - Yousef Marzouk Al-Mutairi, Hend Hassan Alhazmi, Alanoud Abdulwahab Abumelha, Sarah Saleem Aljohani, Tariq Abdurhman S Alwjan, Ali Mohammed Khormi, Meshari Thuhayn D Alotaibi, Khulood Hamoud Hassan Almutairi,; Mousa Ahmed Alahmari, Layla Mohammed Alotibi, Sultan Eissa Alenazi, Abdullah Naseer Bahrri, Saad Mohammed Alrogei, Amal Khalf Alnomsi, Bader Khalifeh Obed Alharbi, Ashwaq Fahad Alaqidi Norah Meari Ali Alneami, (Chelonian Research Foundation, 2022)
Implementing evidence-based therapies for individuals with dementia is an intricate and demanding task. Nevertheless, achieving effective implementation is crucial in order to guarantee evidence-based practice and maintain a high standard of care. Enhancing the implementation procedures in dementia care requires a deeper comprehension of the emerging difficulties. The objective of this research was to uncover current information on the obstacles and factors that support the implementation of nurse-led interventions in dementia care. Only studies that specifically focused on the implementation process and the variables that influenced the adoption of a nurse-led intervention in dementia care across all settings were included. We used an inductive technique to construct domains and categories for the purpose of data analysis. In addition to the usual variables that influence the implementation of nursing treatments, we have uncovered special factors related to dementia that go beyond the obstacles and facilitators that are previously recognized. An established culture that prioritizes individual needs and consistent team cultures and attitudes greatly aid the implementation procedures. Additionally, there is a need for therapies that possess a high degree of adaptability and responsiveness to the condition, requirements, and behavior of patients. Keywords: Dementia, nurse, nurse-led interventions, review, medical care